Existence and Optimization of Zakat, Infaq, Sadaqah in Indonesia for Sustainable Development Goals (SDGs) - Masithoh; Kamsi; Asmuni (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to analyze the development of the Zakat, Infaq, and Sadaqah (ZIS) system in Indonesia through a comprehensive literature review from a historical, legal, and social perspective. The main focus is to explore the evolution of ZIS as an instrument of wealth redistribution and social welfare in Islamic economics. In the context of rising poverty, unemployment, and other socio-economic challenges in modern Indonesia, this study evaluates the adaptation of traditional ZIS practices to contemporary needs, including their contribution to the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework of this research is based on Islamic economic principles, especially those related to wealth redistribution, social justice, and poverty alleviation. Literature Review: The literature review includes an analysis of changes in the implementation of ZIS based on evolving legal frameworks, dynamic social expectations, and changing economic conditions. By bridging historical practices and modern demands, this study highlights the important role of ZIS in addressing poverty and inequality in Indonesia. Methods: The research method uses a qualitative approach through a systematic review of academic publications, government reports, and non-government studies. The data collected is analyzed to identify trends, challenges, and opportunities in the ZIS system. Results: The results show that despite progress in the institutionalization and modernization of ZIS in Indonesia, significant challenges remain. Key problems include inefficiencies in collection and distribution mechanisms, lack of public trust, and inadequate legal and regulatory frameworks. These factors hinder the effectiveness of ZIS in reaching vulnerable groups and maximizing their impact. Implications: The implications of this study include recommendations for policymakers, clerics, and Islamic financial institutions in creating a sustainable and equitable ZIS framework to address the issue of poverty and inequality. Novelty: The novelty of this study lies in the integration of historical, legal, and social perspectives in the analysis of the ZIS system in Indonesia. This research makes a unique contribution by offering a comprehensive understanding of the development and challenges of ZIS in meeting modern needs, as well as opening up further research opportunities for ZIS optimization in realizing social justice and global economic growth for sustainable development goals (SDGs).